Penegakkan Hukum terhadap Pelaku Streamer Judi Slot pada Platform Digital - Ni Made Nisa Dewi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2024)
In the development of technology, one of which is the computer that is used today as technology as a product of science that converges on telecommunications, media and information. The marketing of online gambling is something that is done with the aim of attracting the interest of someone who will use it, can make the base that does this become broad and can provide a very large amount of income for someone who provides services for gambling conducted online. The type of research used in this study is normative legal research. Where it will discuss the following, First, how are the legal arrangements for perpetrators of criminal acts of promotion of online gambling sites carried out by celebrities on digital platforms and how are criminal sanctions for perpetrators of criminal acts of promotion of online gambling sites on digital platforms. The conclusion of this study is that the existence of legal rules that apply to criminal acts that promote online gambling sites can have a major influence on security and economic stability in people's lives, namely gambling acts carried out online.